An expression and function analysis of the CXCR4/SDF-1 signalling axis during pituitary gland development. - Jose Mario Gonzalez-Meljem; Sarah Ivins; Cynthia Lilian Andoniadou; Paul Le Tissier; Peter Scambler; Juan Pedro Martinez-Barbera (PLoS ONE, 2023)
The chemokine SDF-1 (CXCL12) and its receptor CXCR4 control several processes during embryonic development such as the regulation of stem cell proliferation, differentiation, and migration. However, the role of this pathway in the formation of the pituitary gland is not understood. We sought to characterise the expression patterns of CXCR4, SDF-1 and CXCR7 at different stages of pituitary gland development. Our expression profiling revealed that SDF-1 is expressed in progenitor-rich regions of the pituitary anterior lobe, that CXCR4 and CXCR7 have opposite expression domains and that CXCR4 expression is conserved between mice and human embryos. We then assessed the importance of this signalling pathway in the development and function of the murine pituitary gland through conditional deletion of CXCR4 in embryonic pituitary progenitors. Successful and specific ablation of CXCR4 expression in embryonic pituitary progenitors did not lead to observable embryonic nor postnatal defects but allowed the identification of stromal CXCR4+ cells not derived from HESX1+ progenitors. Further analysis of constitutive SDF-1, CXCR7 and CXCR4 mutants of the pathway indicates that CXCR4 expression in HESX1+ cells and their descendants is not essential for normal pituitary development in mice.